Construction of Canine Herpesvirus Vector Expressing Foreign Genes Using a lacZ-TK Gene Cassette as a Double Selectional Marker - Xuan, Xuenan; Nishikawa, Yoshifumi; Takashima, Yasuhiro; Tuchiya, Kotaro; Ueda, Susumu; Yokoyama, Naoaki; Maeda, Ken; Mikami, Takeshi; Otsuka, Haruki (Virus genes, 1998)
An improved method for constructing canine herpesvirus (CHV) recombinants expressing foreign genes by using the lacZ-TK gene cassette as a double selectional marker was developed. A recombinant CHV carrying the lacZ-TK gene at a targeted gene locus was constructed and used as a parental virus for generating new recombinants. The parental virus formed blue plaques and was sensitive to TK-specific drugs, while newly generated recombinants, in which the lacZ-TK gene was replaced with the desired foreign gene, become both resistant to the TK-specific drugs and formed white plaques. Recombinants were isolated by using the combination of drug selection and color selection. This improved method allows construction of recombinant CHV with great ease, because the drug selection can enrich the frequency of recombinant CHV from 0.01-0.1% to 10-80%. This method was employed to construct a recombinant CHV that expressed rabies virus (RV) glycoprotein (G protein).